1993
DOI: 10.1038/363561a0
|View full text |Cite
|
Sign up to set email alerts
|

A tetrameric DNA structure with protonated cytosine-cytosine base pairs

Abstract: Oligomers containing tracts of cytidine form hemiprotonated base pairs at acid pH and have been considered to be double-stranded. We have solved the structure of the DNA oligomer 5'-d(TCCCCC) at acid pH and find that it is a four-stranded complex in which two base-paired parallel-stranded duplexes are intimately associated, with their base pairs fully intercalated. The relative orientation of the duplexes is antiparallel, so that each base pair is face-to-face with its neighbours. The NMR spectrum displays onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
997
1
12

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,133 publications
(1,064 citation statements)
references
References 21 publications
39
997
1
12
Order By: Relevance
“…The recent discovery of positively charged aromatic compounds (for a review [21]) that interact with G-quartet led us to test the binding of cryptolepine and neocryptolepine analogues to G-quadruplexes. A cytidine-rich oligomer forms a radically different quadruplex in which two parallel C-strands associate in a head-to-tail orientation with their C•C + pairs face-to-face, intercalated in a so called i-motif or C-quadruplex [22,23].…”
Section: Fig 1 (A) Formulae Of Cryptolepine (5-methyl Indolo[23b]-mentioning
confidence: 99%
“…The recent discovery of positively charged aromatic compounds (for a review [21]) that interact with G-quartet led us to test the binding of cryptolepine and neocryptolepine analogues to G-quadruplexes. A cytidine-rich oligomer forms a radically different quadruplex in which two parallel C-strands associate in a head-to-tail orientation with their C•C + pairs face-to-face, intercalated in a so called i-motif or C-quadruplex [22,23].…”
Section: Fig 1 (A) Formulae Of Cryptolepine (5-methyl Indolo[23b]-mentioning
confidence: 99%
“…A number of recent studies have revealed that simple short repeats of DNA sequences, like (C-G)~ [4], (C-A)n [5], the telomere repeat, (TTGGGG)n [6,7], (CGA)~ [8,9] and d(TCCCCC) [10], often are associated with unusual DNA structures that may play important biological roles. Here we analyzed in detail the structures associated with the (AATGG)~ sequence by two-dimensional nuclear magnetic resonance spectroscopy (2D NMR) through a quantitative treatment of the nuclear Overhauser effect (NOE) data.…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…It has been assumed in the past that poly(rC) and poly(dC) form hemiprotonated duplexes [36], but there is no decisive structural proof. About fifteen years ago, NMR [27,50] and later x-ray crystal structures [51,52] showed that dC-rich oligonucleotides adopt a quadruplex form ("i-motif DNA") composed of two intercalated duplexes, each of which consists of CH + ·C base pairs. Crystals of d(CT) 3 grown at neutral pH adopt the quadruplex structure [52], showing that i-motif structures do not require acidic conditions for deoxycytidylates.…”
Section: Structural Implicationsmentioning
confidence: 99%
“…It was proposed more than forty years ago that poly(rC) can adopt a double-stranded conformation with parallel strands when the pH is between 4 and 6 [25,26]. More recently, structural NMR studies have shown that cytosine-rich DNAs form an unusual quadruplex structure ("i-motif DNA") consisting of two intercalated duplexes made up of hemiprotonated base pairs [27,28]. This structure, which may be biologically significant [29][30][31], is formed when two parallel-stranded duplexes associate in head-to-tail fashion, forming intercalated hemiprotonated base pairs.…”
Section: Introductionmentioning
confidence: 99%